Analisis Terhadap Usulan Penggunaan Combibox Sebagai Wujud Penerapan Eco Airport Di Indonesia - Wahyoe, Wahyoe (Sekretariat Badan Penelitian dan Pengembangan Perhubungan, 2010)
Air traffic densihj oca1rs at sezieral airports in lndonesin, especinlly nt airports - the airport with thescale of priman; and secondan; sen.rices. Traffic density, of course, affect the time slot to take off andlanding ai.rcraft. At the time of ground, air plane to get some service at the airport, among others,refueling, filling water for toilet and waste water cleaning, loading and unloading goods and luggage,mbin interior aircraft cleaning, catering preparation, checks ai.rcraft engine and much more . Somedeveloped countries in the world has senied the aircraft was grounded with advances in technologythat is able to maintain the qualihJ of the enuironment nt the airport lnj using CombiBox. In addition,this equipment also proved able to econonziz.e energi; expenditure, Human Resources a-IR), andreduce clutter btJ aircraft sen.nee vehicles on the apron.